factorise the question: (1-x^2)(1-y^2)+4xy
Answers
Answered by
40
Hey Juhi !
Here is your solution :
= ( 1 - x^2 ) ( 1 - y^2 ) + 4xy
= 1 - y^2 - x^2 + x^2y^2 + 4xy
= 1 + x^2y^2 - x^2 - y^2 + 4xy
By splitting 4xy,
= 1 + x^2y^2 - x^2 - y^2 + 2xy + 2xy
By regrouping terms ,
= 1 + x^2y^2 + 2xy - x^2 - y^2 + 2xy
= ( 1 + x^2y^2 + 2xy ) - ( x^2 + y^2 - 2xy )
= [ ( 1 )^2 + ( xy )^2 + 2 × 1 × xy ] - ( x - y )^2
Using identity :
( a^2 + b^2 + 2ab ) = ( a + b )^2
= ( 1 + xy )^2 - ( x - y )^2
Using identity :
( a^2 - b^2 ) = ( a + b ) ( a - b ).
= ( 1 + xy + x - y ) ( 1 + xy - x + y ).
====================================
Hope it helps !!
Here is your solution :
= ( 1 - x^2 ) ( 1 - y^2 ) + 4xy
= 1 - y^2 - x^2 + x^2y^2 + 4xy
= 1 + x^2y^2 - x^2 - y^2 + 4xy
By splitting 4xy,
= 1 + x^2y^2 - x^2 - y^2 + 2xy + 2xy
By regrouping terms ,
= 1 + x^2y^2 + 2xy - x^2 - y^2 + 2xy
= ( 1 + x^2y^2 + 2xy ) - ( x^2 + y^2 - 2xy )
= [ ( 1 )^2 + ( xy )^2 + 2 × 1 × xy ] - ( x - y )^2
Using identity :
( a^2 + b^2 + 2ab ) = ( a + b )^2
= ( 1 + xy )^2 - ( x - y )^2
Using identity :
( a^2 - b^2 ) = ( a + b ) ( a - b ).
= ( 1 + xy + x - y ) ( 1 + xy - x + y ).
====================================
Hope it helps !!
juhisai:
brilliant..!!
Answered by
5
Here is your in this photo.
Attachments:
![](https://hi-static.z-dn.net/files/df9/a98f47f83b3419ea5d935908317d8e12.jpg)
Similar questions